Hydrophilic surfaces from simple dip-coating method: amphiphilic block copolymers with zwitterionic group form antifouling coatings under atmospheric conditions. Issue 8 (21st September 2020) - Noguchi, Aya; Masuda, Tsukuru; Chen, Chuqiao; Yoshizawa, Shoichi; Isu, Norifumi; Takai, Madoka
Abstract : Amphiphilic block copolymers with zwitterionic group form antifouling coatings under atmospheric conditions by a dip-coating method. Abstract : Hydrophilic surfaces with antifouling properties are in demand for medical and environmental applications, especially for ready-to-use purposes. In the present study, a simple and effective surface modification of ceramic surfaces via amphiphilic block polymers with zwitterionic group was developed. Block copolymers with polymer chains containing hydrophilic segments of poly(2-methacryloyloxyethyl phosphorylcholine) (MPC) and random copolymer chains of hydrophobic segments of poly(3-(methacryloyloxy)propyl-tris(tri(methylsilyloxy))silane) (MPTSSi) and silane coupling segments of poly(3-methacryloxypropyl trimethoxysilane) (MPTMSi) were synthesized and successfully applied uniformly on glass substrates. For the block polymer chains with longer hydrophilic segments, the surfaces exhibited high hydrophilicity under dry conditions and excellent antifouling properties without hydration pretreatment. The zwitterionic block copolymer-modified surface showed good durability and protein inhibition properties for pH of 2–9. The hydrophilic surface coating based on the developed block copolymers is suitable for medical, healthcare, sanitary, and environmental applications because it requires no pre-hydration.